Farm-planning under risk: An application of decision analysis and portfolio theory for the assessment of crop diversification strategies in horticultural systems. (May 2022) - Burbano-Figueroa, Oscar; Sierra-Monroy, Alexandra; David-Hinestroza, Adriana; Whitney, Cory; Borgemeister, Christian; Luedeling, Eike
Abstract: CONTEXT: Even though diversification of horticultural production systems allows farmers to cope with risks and uncertainties, strategies for raising profitability usually aim to improve the productivity of monocultures rather than pursuing diversification. Horticultural production systems are often highly diversified in terms of land use and planted crops. OBJECTIVE: Assessing the economic prospects of these complex systems requires quantification of productivity and related risks for individual crops as well as an assessment of the benefits from diversification. Here we demonstrate the implementation of a systematic assessment for irrigated production systems in the Sinú Valley of the Colombian Caribbean. METHODS: We used participatory modeling approaches, focus group discussions and interviews to collect relevant qualitative and quantitative information from farmers. Quantitative information associated with input variables was elicited as probability distributions. Farmers were trained in estimation techniques, enabling them to provide reliable quantitative assessments of production-related variables. RESULTS AND CONCLUSIONS: The model and elicited values for input variables were used to build a probabilistic simulation that allowed for estimating the expected income from horticultural crops and identifying portfolio strategies based on currently available horticultural options. The irrigated horticultural production systems of the Sinú Valley in Colombia contain four main crops. All farmers cultivate eggplants and sweet peppers but they have specific preferences for yardlong beans and papaya. These preferences reflect two crop diversification strategies attuned to farmers' resources. Yardlong beans are a short-term (3 months), low-risk, and low-profit investment (a tenth of the best crop option) while papaya is a long-term crop (18 months) of high-risk and profit. Yardlong beans are planted by smallholders with limited financial resources as a way to subsist and produce additional cash that can be invested in riskier more profitable crop options (eggplants and sweet peppers). This strategy describes a transition from a secure option (3 standard deviations (SD)) to riskier options (6 SD or more) that can generate greater profits. The second strategy describes actions of wealthier smallholders that can invest in short-lived perennial crops including papaya, sweet pepper and eggplants. This three-crop portfolio cuts production risks roughly in half (from 10 SD for the riskier option to 5 SD in the portfolio). SIGNIFICANCE: We expect our decision analysis approach to prove useful in assessing other horticultural systems but also for the assessment and identification of new crop options to be incorporated in diversified systems. Our decision analysis approach can also be used to represent diversification in other whole-farm planning scenarios, e.g. when it comes to rotations of field crops, integrated livestock farms, cut-flower farming or agroforestry systems. Graphical abstract: Unlabelled Image Highlights: We used a participatory modeling approach to collect relevant qualitative and quantitative information from farmers. Farmers were trained to provide assessments of production-related variables that were elicited as probability distributions. We used decision analysis to assess crop productivity and the diversification benefit of risk reduction in horticulture. We identified diversification strategies suited to technical or economical limitations or individual farmer's preferences Our decision analysis approach can be used to represent diversification in other whole-farm planning scenarios.